Dry Heat: Baking, Roasting, and Broiling - J. Marie Arick; Kendra Zamojski; Amarat Simonne (EDIS, 2021)
This publication is the first in a series of documents to complement A Healthy Table Virtual Cooking School. The purpose is to educate the general public on how to safely prepare healthy meals at home. Written by M. Arick, K. Zamojski, and A. Simonne, and published by the UF/IFAS Department of Family, Youth and Community Sciences, November 2021.